Intention to treat outcome of T1 hepatocellular carcinoma with the "wait and not ablate" approach until meeting T2 criteria for liver transplant listing. Issue 2 (8th January 2016) - Mehta, Neil; Sarkar, Monika; Dodge, Jennifer L.; Fidelman, Nicholas; Roberts, John P.; Yao, Francis Y.
Abstract : Patients with T1 hepatocellular carcinoma (HCC; 1 lesion < 2 cm) are currently not eligible for priority listing for liver transplantation (LT). A common practice is to wait without locoregional therapy (LRT) until tumor growth occurs from T1 to T2 (1 lesion 2‐5 cm or 2‐3 lesions ≤ 3 cm) to be eligible for listing with Model for End‐Stage Liver Disease exception. We aimed to evaluate the intention to treat outcome of the "wait and not ablate" approach for nonresection candidates with T1 HCC until tumor growth to T2. The study included 114 patients with T1 HCC 1.0‐1.9 cm followed by serial imaging every 3 months. Two investigators performed independent imaging reviews to confirm the diagnosis. Median increase in total tumor diameter was 0.14 cm/month. Probabilities of progression from T1 to directly beyond T2 without LT listing were 4.4% at 6 months and 9.0% at both 12 and 24 months. The 1‐ and 3‐year survival was 94.5% and 75.5%. In multivariate analysis, predictors of rapid tumor progression, defined as a >1 cm increase in total tumor diameter over 3 months, included alcoholic liver disease (odds ratio [OR], 6.52; P  = 0.02) and Hispanic race (OR, 3.86; P  = 0.047), whereas hepatitis B appeared to be protective (OR, 0.09; P  = 0.04). By competing risks regression, predictors of exclusion from LT (with or without listing for LT under T2) were alpha‐fetoprotein (AFP) ≥ 500 ng/mL (HR, 12.69; 95% confidence interval, 2.8‐57.0; P  = 0.001) and rapid tumor progression (HR, 5.68; P  < 0.001). In conclusion, the "wait and not ablate" approach until tumor growth from T1 to T2 before LT listing is associated with a <10% risk of tumor progression to directly beyond T2 criteria. However, patients with AFP ≥ 500 ng/mL and rapid tumor progression are at high risk for wait‐list dropout and should receive early LRT. Liver Transpl 22:178‐187, 2016 . © 2015 AASLD.